Inovasi Pembelajaran Aksara Jawa dengan Permainan Edukatif Digital berbasis Augmented reality pada Peserta Didik SMP Negeri 1 Nglipar - Davin Elian Qariru; Muhammad Fajrulfalaq Izzulfirdausyah Suryaprabandaru; Fikriansyah Ridwan Pratama; Salsabila Eka Fadila; Veronica Tia Ningrum; Ahmad Nasikun; Akhmad Bagus Nuryanto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Javanese script is less popular among students, including those at SMP Negeri 1 Nglipar. An interview with Mr. Sartono (a Javanese language teacher at SMP Negeri 1 Nglipar) revealed that daily, mid-semester, and end-of-semester tests on Javanese script have the lowest average scores compared to other subjects. The lack of instructional media that facilitates the teaching and learning process at SMP Negeri 1 Nglipar also contributes to the decreased interest among students. According to a survey, the majority of students prefer learning through game-based methods, particularly adventure boards. Therefore, the idea of an educational medium through adventure boards combined with AR (augmented reality) technology, or AJAR, was proposed to increase the interest and understanding of 7th-grade students at SMP Negeri 1 Nglipar in Javanese script. The materials and questions were validated by the Yogyakarta Palace, while the educational media was validated by BTKP Yogyakarta. As a result, they could be implemented in teaching. AJAR was then used in teaching. The class using AJAR (37.50) showed a higher improvement in scores from pretest to posttest compared to the conventional class (23.00). All activity indicators in the AJAR class were also higher. Therefore, AJAR can increase the interest and understanding of 7th-grade students at SMP Negeri 1 Nglipar in Javanese script.